Conservation management - Bandar Diraja Pekan / Nadiatul Aswani Mohd Yusuff - Mohd Yusuff, Nadiatul Aswani (Faculty of Architecture, Planning and Surveying, 2008)
Pekan Bandar Diraja is an area where all the old buildings, streets and monuments are conserved by the Museum Pahang State Board. Rapid development has changed the livelihoods of the local community and all the values brought abut by development has not integrated with the local community. Furthermore, rapid development in Pekan has left many old building in a poor condition, often redundant. Taking an initiative to highlight the needs of an appropriate conservation management, this study will present a preliminary evaluation of a questionnaire intended to examine the perception of residents in Pekan, Pahang towards conservation practice in their areas. Data collection is based on questionnaires submit to the residents of Pekan. The objectives of this study are (a) to have an in depth study on how to conserve a building and an area by taking into consideration all important and related aspect, (b) the understanding in conservation management in Pekan, Pahang in order to know how they conserve the building and maintain the building conservation at that area and (c) also identify perception of residents in Pekan, Pahang towards conservation practice in Pekan, Pahang. As the findings, it was show that the residents at Bandar Diraja Pekan, Pahang were not really concern about conservation in their area because lack of knowledge, budget, not good in planning, hard to maintain the building, higher cost in maintenance and less of promotion but they really think that it is important to conserve the building so that our history and culture will be preserve.The following recommendations were made: 1. Establish in g a pro p e r co n servation department under the Federal Authorities specifically to manage, control and regulates guidelines for conservation works in Malaysia 2. The most essential change is perhaps changing the perception of the government officers. The current situation in Malaysia proves that conservation is not a priority for the government 3. A specific Conservation Act should be regulated for the purpose of conserving the buildings and sites in Malaysia. All the legislations on conservation and preservation need to be compiled, standardized and analysed before regulating a new one.